2013
DOI: 10.1002/pi.4555
|View full text |Cite
|
Sign up to set email alerts
|

Structural and photoresponsive behavior of a series of (phenylene)azobenzene-containing liquid-crystalline methacrylic copolymers

Abstract: A series of side-chain liquid-crystalline methacrylic copolymers, having various amounts of 4 -(4-decyloxyphenyl)-4-(hexyloxy)azobenzene as the mesogenic group, were synthesized and characterized by differential scanning calorimetry, polarizing optical microscopy and X-ray diffraction to determine their mesomorphic properties, and by UV−visible spectrometry to elucidate their optical absorption characteristics. Also, birefringence and surface relief gratings were photoinduced in the films using a laser beam of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Nevertheless, it seems that a coordinated motion of the close packed chromophores in P4VP‐100 produces a higher orientation (birefringence), despite the structural constrains. This result corroborate that there is a tight interplay between photo‐induced orientation and intrinsic molecular order in films, as indeed it was demonstrated to occur in other liquid crystal polymers where the prevalence of cooperative motions depends on the ability of chromophores to move in concert at specific experimental conditions . Although small, the obtained Δ n 30min values are comparable to those reported for other random and block liquid‐crystalline azopolymers …”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Nevertheless, it seems that a coordinated motion of the close packed chromophores in P4VP‐100 produces a higher orientation (birefringence), despite the structural constrains. This result corroborate that there is a tight interplay between photo‐induced orientation and intrinsic molecular order in films, as indeed it was demonstrated to occur in other liquid crystal polymers where the prevalence of cooperative motions depends on the ability of chromophores to move in concert at specific experimental conditions . Although small, the obtained Δ n 30min values are comparable to those reported for other random and block liquid‐crystalline azopolymers …”
Section: Resultssupporting
confidence: 87%
“…This means that for this low chromophore content polymer the interaction between the azobenzene groups is weak, responding to irradiation like independent units. For the other films (P4VP‐50 and P4VP‐100), the UV‐Vis spectra is shifted to lower wavelengths (hypsochromic shift), suggesting a major interaction between chromophores . Actually, hypsochromic or blue shifts are regularly associated to the formation of H‐aggregates, where chromophores respond to light not as independent units but coupled the ones to the others .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are in addition several examples where the authors proved that their material was in a crystalline phase. , Nakano et al, for instance, observed the formation of SRG at the surface of a single crystal of 4-(dimethylamino)­azobenzene (Figure y). Several papers were aimed at comparing molecular materials to their poly­meric counter­parts. , Many examples have been des­cribed where the systems are in a liquid-crystal­line phase. ,,,,,, Ruthenium acetyl­ides derivatives can also be used for the inscription of SRG. ,, These com­pounds are used in the field of non­linear optics because they are stable, easily prepared, and redox-responsive. Sahraoui et al synthesized such complexes with azobenzene derivatives (Figure z) and studied the ability to form relief gratings on these materials .…”
Section: Motion From Photochromic Molecular Switchesmentioning
confidence: 99%